2020
DOI: 10.1371/journal.pone.0230825
|View full text |Cite
|
Sign up to set email alerts
|

Urban farms in Miami-Dade county, Florida have favorable environments for vector mosquitoes

Abstract: The creation of urban farms in complex urban built environments may create suitable local conditions for vector mosquitoes. Urban farms have been implicated in the proliferation of mosquitoes in Africa, but there is a dearth in the knowledge of their role in the proliferation of mosquitoes elsewhere. In this study, we surveyed two urban farms in Miami-Dade County, Florida. Our results show that urban farms provide favorable conditions for populations of vector mosquito species by providing a wide range of esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Even adjacent remote and urban collection sites had completely distinct mosquito community composition, species richness, and relative abundance. These results support the hypothesis that the availability of resources at the micro-geographic scale (i. e., neighborhood-level) is a major driver for the proliferation or decrease of populations of vector mosquito species according to their specific ecology and behavior 22 , 58 . For example, both Ae.…”
Section: Discussionsupporting
confidence: 84%
“…Even adjacent remote and urban collection sites had completely distinct mosquito community composition, species richness, and relative abundance. These results support the hypothesis that the availability of resources at the micro-geographic scale (i. e., neighborhood-level) is a major driver for the proliferation or decrease of populations of vector mosquito species according to their specific ecology and behavior 22 , 58 . For example, both Ae.…”
Section: Discussionsupporting
confidence: 84%
“…A recent relevant study of urban farms in Miami-Dade County, Florida, USA, reported that storm drains, phytotelmata, discarded tyres and garbage cans contained significant numbers of Ae. aegypti [ 31 ]. Phytotelmata were not investigated in our study due to the limited availability of personnel for the study, but they are also likely to serve as habitats for Aedes in the Jaffna peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus , typically regarded to be a peri-urban vector of dengue, has expanded its range to built-up areas of Jaffna city. Urban farms have been reported to provide favourable environments for Aedes mosquitoes in Florida, USA [ 31 , 32 ], and this also appears to be the case in the Jaffna peninsula. A previous GIS-based study showed that the built-up areas of Jaffna city have a high local incidence of dengue [ 33 ], which is consistent with the present findings that show high ovitrap indices in the city.…”
Section: Discussionmentioning
confidence: 99%
“…Human behavior and socioeconomic conditions should also be considered. Workers that spent a disproportionate amount of time outdoors, such as those in the construction and agriculture workforce, are often more exposed to vector mosquitoes and may be more exposed to arboviruses 63 66 . Therefore, it is essential to remove the most productive aquatic habitats from areas with high concentrations of outdoor workers, such as construction sites, outdoor sports events, and outdoor entertainment areas.…”
Section: Discussionmentioning
confidence: 99%
“…This system provides valuable insight into the population dynamics of vector mosquitoes in Miami 48 . Moreover, many studies have been conducted in areas considered problematic for controlling vector mosquitoes in Miami such as construction sites 79 , tire shops 80 , ornamental bromeliad patches 55 , cemeteries 81 , and urban farms 66 . Together, these studies have provided key evidence of vector mosquito distribution in Miami.…”
Section: Methodsmentioning
confidence: 99%